The Comparison of Latent Fingerprints by Using Poreology - Bunteng, Kwandao; Choosakoonkriang, Sirirat (วารสารวิทยาศาสตร์และเทคโนโลยี สถาบันอุดมศึกษาเอกชนแห่งประเทศไทย, 2023)
The objective of this study was to analyze the sweat pore features in context to their position for the identification of individuals. Latent fingerprints collected from different surfaces including white paper envelopes, doorknobs, knives and mirrors were employed in this study. Because of the evidence that can be found a lot in crime scene and that fingerprints obtained from these evidences have insufficient minutiae. Therefore, the researcher studied latent fingerprints on the evidence by using the following methods: 1) black powder method 2) magnetic powder method and 3) ninhydride solution method. Then photographed with a fingerprint detection and image acquisition device (DCS4) and had a fingerprint specialist compare latent fingerprints with fingerprints printed. The results showed that latent fingerprints can be detected in each method when taking pictures and adjusting with Adobe Photoshop, studying only the areas that have special features are not enough to identification. When using the position of sweat pore included, fingerprint forensics specialists can verify according to the ACE-V scientific methodology.This research will be useful for further advanced fingerprint verification.